2013
DOI: 10.5216/ree.v15i2.23898
|View full text |Cite
|
Sign up to set email alerts
|

Controle glicêmico no perioperatório: evidências para a prevenção de infecção de sítio cirúrgico

Abstract: Controle glicêmico no perioperatório: evidências para a prevenção de infecção de sítio cirúrgico ABSTRACTThe objective of the present study was to analyze the evidence available in literature regarding blood glucose control to prevent surgical site infection in the perioperative period. The integrative literature review was the chosen review method.The primary studies were searched on the following databases: Medline, CINAHL, EMBASE and LILACS. Of the 26 primary studies included in the review, 12 were conduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
8

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
8
0
8
Order By: Relevance
“…Naturally, alterations vary with the intensity and level of control of the disease. Therefore, it is important to assess the health condition of these patients and the need for surgical intervention, and to analyze the cost–benefit of surgeries such as THA 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, alterations vary with the intensity and level of control of the disease. Therefore, it is important to assess the health condition of these patients and the need for surgical intervention, and to analyze the cost–benefit of surgeries such as THA 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent integrative review found that 23 out of 26 studies emphasized the need for glycemic control, observing an association of hyperglycemia with infections in the postoperative period, highlighting SSIs, increased morbidity, mortality, and costs during hospitalization (5) . A systematic review published in 2009 included only five studies and aimed to verify the relationship between glycemic control and the incidence of surgical site infections, mortality and length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…They are related to the procedure to be performed, such as type of surgery, its duration, employed techniques, preoperative preparation, and factors related to inoculum of microorganisms, such as their virulence and resistance originating from the environment and the patient's microflora. There are also factors related to patients themselves, as extremes of age, smoking, obesity, malnutrition, use of immunosuppressive drugs, and the presence of chronic diseases such as diabetes mellitus (DM) and hyperglycemia, which motivated this study (3)(4)(5)(6)(7) . In this sense, with significant improvements in quality of life and technological advances, combined with higher survival, there is increased population with chronic diseases (such as diabetes mellitus) that will undergo surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations